2021
DOI: 10.1038/s41467-021-23086-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutrophil extracellular traps in radiation resistance of invasive bladder cancer

Abstract: Radiation therapy (RT) is used in the management of several cancers; however, tumor radioresistance remains a challenge. Polymorphonuclear neutrophils (PMNs) are recruited to the tumor immune microenvironment (TIME) post-RT and can facilitate tumor progression by forming neutrophil extracellular traps (NETs). Here, we demonstrate a role for NETs as players in tumor radioresistance. Using a syngeneic bladder cancer model, increased NET deposition is observed in the TIME of mice treated with RT and inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 67 publications
4
100
0
Order By: Relevance
“…Additionally, these authors found that patients with persistent disease had a high pre-treatment intratumoral PMN to CD8 ratio. In line with this experimental data is the clinical observation that a high PMN to CD8 ratio was associated with worse overall survival [85]. The NET barrier at the interface of tumor cells and necrotic tissue was also noted by the previously mentioned study of Berger-Achituv et al in Ewing sarcoma biopsy samples [18].…”
Section: Nets Is Physically Blocking T-cell Infiltration To the Tmesupporting
confidence: 76%
See 4 more Smart Citations
“…Additionally, these authors found that patients with persistent disease had a high pre-treatment intratumoral PMN to CD8 ratio. In line with this experimental data is the clinical observation that a high PMN to CD8 ratio was associated with worse overall survival [85]. The NET barrier at the interface of tumor cells and necrotic tissue was also noted by the previously mentioned study of Berger-Achituv et al in Ewing sarcoma biopsy samples [18].…”
Section: Nets Is Physically Blocking T-cell Infiltration To the Tmesupporting
confidence: 76%
“…These authors claimed that NETs may play a role in tumor radioresistance by blocking intratumoral CD8 T-cell infiltration post-RT. This effect was related to the clinical effect of the RT [85]. A higher intratumoral PMN to CD8 ratio was observed in RT non-responders compared to RT responders.…”
Section: Nets Is Physically Blocking T-cell Infiltration To the Tmementioning
confidence: 89%
See 3 more Smart Citations